Study of the electrochemical behaviour of amphetamine and its derivatives in aqueous solution - Keller, Thomas; Mutz, Martin; Aderjan, Rolf; Latscha, Hans Peter (Fresenius' journal of analytical chemistry, 1999)
The polarographic behaviour of amphetamine-type drugs in acid and alkaline solutions was investigated. Differential pulse polarography (DPP) with a dropping mercury electrode (DME) was used to monitor these drugs in aqueous solution. DPP and cyclic voltammetry (CV) were also utilised to study the electrode process of some 2-phenylethylamines derivatised with 4-N,N-dimethylaminobenzaldehyde (Ehrlich’s reagent) and 2,4-dinitrofluorobenzene, known as Sanger’s reagent, respectively.
Gesehen am 23.04.2021